The rise of a new generation: Intergenerational value change in Egypt - Elkelani, Zeyad M. (AUC Knowledge Fountain, 2015)
Arab Spring is commonly associated to youth mobilization and their dissatisfaction with respective Arab authoritarian regimes. This empirical study explores such claim through tracing various social, political and demographic indicators as determinants of generational value change in post-2011 Egypt. It employs a generational perspective in discovering such values following Karl Mannheim‟s definition of generations. Mannheim argued that a political generation is composed of a birth cohort sharing similar values through a multifaceted historical process of socialization. The theoretical framework guiding considerable portion of this study is Ronald Inglehart‟s “intergenerational value change thesis.” Inglehart argues that there is an ongoing transnational value shift towards “postmaterialism,” which includes self-expression, quality of life and sense of belonging values with less emphasis on “materialist” values of traditionalism and security concerns. For Inglehart, younger generations are more likely to be postmaterialists given that their formative experiences are shaped through socioeconomic prosperity if compared to older cohorts. In this study, I aim to address central inquiry on whether youth values are different from their older peers and its relevance to the 2011 events in Egypt. In doing so, this reaserach below, starts by inspecting the relevance of postmaterialism argument to Egyptian youth within international and regional contexts. Secondly, it maps out generational trends in relevance to political values. And finally investigate social parameters‟ effects aiming at scrutinizing changing youth values in post 2011 Egypt. Most of studies on youth in Egypt and the Middle East are yet historical or anecdotal. In this project below, we examine secondary data from the World Values Survey and the Arab Barometer collected between 2001 and 2013. In order to untangle the unique effects of our proposed forecasters, we run multiple regressions instead of conventional bivariate associations and percentage distributions. On the whole, we find very limited support for Inglehart‟s thesis in explaining the Egyptian case. Although younger generation shows more propensities for postmaterialism, nevertheless the relative salience of such values is low in Egypt. We call for reconsidering Inglehart‟s model in developing nations. Moreover, we find evidence for cohort value variance in regard to some political and social values. However, part of these differences is related to intra-cohort aging effects. Thus, we cast doubt for the youth uniqueness claim and call for its refinement. Furthermore, we cast additional doubt for the claim on the liberal nature of young Egyptians. In addition, we find considerable support for youth fragmentation in Egypt. Much of the division among them is explained by demographic factors. Overall, this study opens the door for future qualitative studies through investigating our proposed criticisms and doubts on the existing claims on the youth distinctiveness in Egypt who agitated the 2011 uprising.